2016
DOI: 10.1167/16.3.16
|View full text |Cite
|
Sign up to set email alerts
|

Degraded attentional modulation of cortical neural populations in strabismic amblyopia

Abstract: Behavioral studies have reported reduced spatial attention in amblyopia, a developmental disorder of spatial vision. However, the neural populations in the visual cortex linked with these behavioral spatial attention deficits have not been identified. Here, we use functional MRI–informed electroencephalography source imaging to measure the effect of attention on neural population activity in the visual cortex of human adult strabismic amblyopes who were stereoblind. We show that compared with controls, the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
100
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(111 citation statements)
references
References 97 publications
(169 reference statements)
9
100
2
Order By: Relevance
“…Future research will establish if the reduced attentional modulation found for contrast detection (Hou et al, 2016) is also present for the discrimination task we employed here. We encourage future studies investigating these and other aspects of attention with neurotypical and special populations to take advantage of precise terminology and well-established experimental protocols, such as those employed in this study, which allow experimenters to reliably isolate, manipulate, and measure particular types of attention.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Future research will establish if the reduced attentional modulation found for contrast detection (Hou et al, 2016) is also present for the discrimination task we employed here. We encourage future studies investigating these and other aspects of attention with neurotypical and special populations to take advantage of precise terminology and well-established experimental protocols, such as those employed in this study, which allow experimenters to reliably isolate, manipulate, and measure particular types of attention.…”
Section: Discussionmentioning
confidence: 84%
“…They found that amblyopes significantly underestimated the number of targets when using their amblyopic eye compared to the nonamblyopic eye and controls across all cueing conditions, which they argue to be evidence for a “high-level deficit.” Note that even though their amblyopes do exhibit a robust and reliable endogenous attention effect (valid vs. invalid cueing) of the same magnitude as that shown by visually intact observers, this study is often cited as one of the primary studies providing evidence for a visual attention deficit in amblyopia (Farzin & Norcia, 2011; Ho et al, 2006; Hou et al, 2016; Levi, 2013; Levi & Tripathy, 2006; McKee, Levi, Schor, & Movshon, 2016; Secen et al, 2011; Tripathy & Levi, 2008). …”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations